Perancangan Rumah Tipe 45 di Kota Palangka Raya Menggunakan Metode Building Information Modelling - Kisworo, Kesa Endri; Gawei, Apria Brita Pandohop (Jurnal Basement : Jurnal Teknik Sipil, 2025)
The population growth of Palangka Raya City has increased, this affects the need for housing, with type 45 houses being the main choice. In facing these challenges, planners need an innovation, namely by using the BIM method. The use of BIM was chosen because of its ability to integrate modeling, and can overcome the problem of lack of detail at the design stage that often occurs in the construction industry. The selection of a combination of Tekla Structures and Archicad 27 software optimizes the design process. With Tekla Structures for structural modeling to reinforcement and Archicad focusing on architectural modeling. The purpose of this research is to design 3D structural, architectural, and MEP models of type 45 houses using the Building Information Modeling method, which will be carried out using Tekla Structures Educational Version and Archicad 27 Educational Version software. This research uses secondary data in the form of DED data for type 45 houses obtained from planning consultants, type 45 houses are located on Jalan Untung Suropati, Palangka Raya. The data analysis technique using the BIM method consists of 3 stages, namely modeling the building structure and reinforcement using Tekla Structures software, architectural modeling using Archicad 27, and MEP modeling using Archicad 27. The results showed that this research produced a 3D design of structural, architectural, and MEP models for type 45 houses using the BIM method